Which is the optimum parenting for adolescents with low vs. high self-efficacy? Self-concept, psychological maladjustment and academic performance of adolescents in the Spanish context - Reyes, Maria; Garcia, Oscar Fernando; Perez-Gramaje, Amador Fernando; Serra, Emilia; Melendez, Juan Carlos; Alcaide, Marta; Garcia, Fernando (Anales de Psicología / Annals of Psychology, 2023)
The aim of this paper is to establish which parenting style is associated with optimum outcomes among adolescents of Spanish families considering adolescents with low vs. high self-efficacy. Although classical studies identify the authoritative parenting style (based on warmth and strictness) as the best parental strategy, emerging research seriously questions the benefits of parental strictness. Additionally, the impact of parenting on the adolescent’s psychosocial competence has been studied for years, but less is known about whether it might vary depending on individual characteristics of the adolescent (e.g., self-efficacy). Participants were 1029 Spanish adolescents, 453 males (44%), aged 12-17 years. Families were classified in one of the parenting styles groups (authoritative, authoritarian, indulgent, or neglectful), and adolescents were grouped by low vs. high self-efficacy. Adolescent psychosocial competence was examined through emotional and academic self-concept, psychological maladjustment (hostility/aggression, negative self-esteem, emotional responsivity, instability, and negative view of the world), and academic performance (grade point average and number of failing grades). Main and interaction effects of parenting style and adolescent self-efficacy were tested. Main effect results indicated that adolescents with low self-efficacy were always associated with the worst psychosocial competence. Consistently, the main effect findings indicated that adolescents from indulgent and authoritative families were associated with better results than those from neglectful and authoritarian families. However, the indulgent parenting style yielded the best results. The impact of parenting might not be the same for adolescents in all cultural contexts. Contrary to findings from classical studies, parental strictness seems to be unnecessary or even detrimental for adolescents with low and high self-efficacy.